Reweaving the Fabric of Mitochondrial Contact Sites in Astrocytes - Bergami, Matteo; Motori, Elisa (Frontiers in Cell and Developmental Biology, 2020)
The endoplasmic reticulum (ER) and mitochondria are classically regarded as very dynamic organelles in cell lines. Their frequent morphological changes and repositioning underlie the transient generation of physical contact sites (so-called mitochondria-ER contacts, or MERCs) which are believed to support metabolic processes central for cellular signaling and function. The extent of regulation over these organelle dynamics has likely further achieved a higher level of complexity in polarized cells like neurons and astrocytes to match their elaborated geometries and specialized functions, thus ensuring the maintenance of MERCs at metabolically demanding locations far from the soma. Yet, live imaging of adult brain tissue has recently revealed that the true extent of mitochondrial dynamics in astrocytes is significantly lower than in cell culture settings. On one hand, this suggests that organelle dynamics in mature astroglia in vivo may be highly regulated and perhaps triggered only by defined physiological stimuli. On the other hand, this extent of control may greatly facilitate the stabilization of those MERCs required to maintain regionalized metabolic domains underlying key astrocytic functions. In this perspective, we review recent evidence suggesting that the resulting spatial distribution of mitochondria and ER in astrocytes in vivo may create the conditions for maintaining extensive MERCs within specialized territories – like perivascular endfeet – and discuss the possibility that their enrichment at these distal locations may facilitate specific forms of cellular plasticity relevant for physiology and disease.